2002
DOI: 10.1523/jneurosci.22-24-10529.2002
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Serotonin 2C Receptor Editing by Sustained Changes in Serotonergic Neurotransmission

Abstract: Serotonin 2C (5-HT 2C ) receptor pre-mRNA is a substrate for RNA editing enzymes that convert five adenosines (named A, B, CЈ, C, and D editing sites) to inosines. Editing of two of these sites (CЈ and C) is crucial for decreasing the efficiency of the receptor to activate G-protein. Nucleotide sequence analysis of mouse forebrain neocortical 5-HT 2C mRNA isoforms revealed that editing at these two sites is regulated in a serotonindependent manner. In serotonin-depleted mice, CЈ-and C-site editing is significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
125
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 9 publications
(17 reference statements)
4
125
0
1
Order By: Relevance
“…In this context, it is noteworthy that 5-HT 2C Rs undergo a region-dependent RNA editing (Burns et al, 1997), a mechanism that generates distinct functional populations of 5-HT 2C Rs with different levels of constitutive activity Navailles et al, 2006b) and different desensitization rate (Marion et al, 2004). Specifically, the pattern of 5-HT 2C R edited isoforms may determine the response to endogenous 5-HT (Herrick-Davis et al, 1999) and control the signal-tonoise ratio at central 5-HT synapses (Gurevich et al, 2002;Niswender et al, 1999). In the NAc, 5-HT 2C R, transcripts are densely expressed in the anterior compartment and appear to localize to medium-sized neurons that express the distribution, localization, and morphology typical of striatal GABA efferent neurons (Eberle-Wang et al, 1997;Morilak et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is noteworthy that 5-HT 2C Rs undergo a region-dependent RNA editing (Burns et al, 1997), a mechanism that generates distinct functional populations of 5-HT 2C Rs with different levels of constitutive activity Navailles et al, 2006b) and different desensitization rate (Marion et al, 2004). Specifically, the pattern of 5-HT 2C R edited isoforms may determine the response to endogenous 5-HT (Herrick-Davis et al, 1999) and control the signal-tonoise ratio at central 5-HT synapses (Gurevich et al, 2002;Niswender et al, 1999). In the NAc, 5-HT 2C R, transcripts are densely expressed in the anterior compartment and appear to localize to medium-sized neurons that express the distribution, localization, and morphology typical of striatal GABA efferent neurons (Eberle-Wang et al, 1997;Morilak et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…42 Specifically, the frequencies of less edited or unedited isoforms with higher sensitivity to serotonin were increased when serotonin was depleted by as much as 80%. Conversely, a serotonin agonist increased the frequency of more edited isoforms that activate G-protein coupling less efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…47 Because increased 5-HT 2C R editing can hamper the responsivity of this receptor subtype to serotonin, our findings suggest that antidepressant therapies, especially those that involve serotonin reuptake inhibition, may be less effective in blunting suicidal tendencies in a subpopulation of patients with an inherently high level of the VSV isoform. Moreover, the proportion of the VSV isoform could be additionally enhanced in these individuals during the initial stages of SSRI therapy as an adaptation to the augmented levels of serotonin in the synapse 22,42 contributing to suicidality in this vulnerable subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in patterns of HTR2C editing have been reported in subsets of patients with schizophrenia and depression (Gurevich et al 2002a;Niswender et al 2001;Dracheva et al 2003), and baseline differences have also been reported among different inbred mouse strains (Englander et al 2005;Hackler et al 2006;Du et al 2006). Changes in editing patterns have been induced, in rodents, by exposure to tests of anxiety, including the forced swim test and learned helplessness, and by drugs, such as fluoxetine (Gurevich et al 2002b;Iwamoto et al 2005;Englander et al 2005;Yang et al 2004). Most of the changes in editing patterns induced by disease, genetic background, stress and pharmacological treatment are subtle and the corresponding diversity at the protein level has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%